Seasonal variation in a diverse beetle assemblage along two elevational gradients in the Australian Wet Tropics - Wardhaugh, C W; Stone, M J; Stork, N E (Scientific reports, 2018)
Altered abiotic conditions resulting from human-induced climate change are already driving changes in the spatial and temporal distributions of many organisms. For insects, how species are distributed across elevations is relatively well known, but data on their seasonality at different elevations are lacking. Here we show seasonal variation in beetle abundance and species richness along two spatially-distinct elevational transects (350-1000 m and 100-1000 m asl) in the rainforests of northern Australia. Temperature was the best predictor of temporal abundance and species richness patterns, while rainfall had little influence. Elevation had little effect on seasonal changes in abundance or diversity. Adults of most beetle species exhibited long season-lengths (>6 months of the year) with distinct peaks in abundance during the summer wet-season. We found evidence of phenotypic variation among the more widespread species, with seasonal peaks in abundance often not coinciding across elevations or transects. Due to the wide elevational range of most species, and the lack of consistency in the seasonality of wide-spread individual species, we suggest that many beetles inhabiting the low to mid-elevation mountains in the Wet Tropics, and potentially other tropical rainforests, are not as vulnerable to extinction due to climate change as many other organisms.
Keywords: deštný prales; Austrálie; Animals; Behavior, Animal; tropické klima; Australia; brouci; lidé; Seasons; chování zvířat; zvířata; Tropical Climate; Rainforest; Coleoptera; roční období; Humans